Influence of socio-economic factors on learner indiscipline in selected secondary schools in South Africa - Mfundo Sihle Khumalo; Patricia Namayammu Mokgosi (Center for Sociological Studies and Community Developmen, 2026)
Learner indiscipline remains a persistent challenge in South African secondary schools, particularly within socio‑economically disadvantaged contexts. Existing research often addresses indiscipline in general terms, with limited attention to how specific local socioeconomic conditions shape behavioral outcomes. This qualitative study examines the influence of poverty, unemployment, and family instability on learner indiscipline in selected secondary schools in the Ekurhuleni South District. Data were generated through semi‑structured interviews and focus group discussions with principals, teachers, school management team members, and school governing body representatives, and analyzed thematically. The findings reveal that socioeconomic hardship contributes to emotional distress, disengagement, irregular attendance, and diminished motivation among learners, which manifest as disruptive behavior. Indiscipline is shown to be structurally produced rather than solely the result of individual moral failure or weak school discipline. While schools retain some capacity to mediate these effects through relational, consistent, and restorative disciplinary practices, such efforts are constrained by overcrowding, limited resources, and inadequate psychosocial support. The study argues for context‑sensitive, multi‑level responses that integrate disciplinary reform with socio‑economic support, strengthened home school partnerships, understanding learner indiscipline as a social justice issue has important implications for education policy and practice in South Africa.